1968
DOI: 10.1126/science.160.3827.541
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking: Stimulatory Effect on Metabolism of 3,4-Benzpyrene by Enzymes in Human Placenta

Abstract: The enzymatic hydroxylation of 3,4-benzpyrene was not detected in human placentas obtained after childbirth from nonsmokers, whereas this enzyme activity was present in placentas obtained from individuals who smoked cigarettes. The degree of induction of benzpyrene hydroxylase caused by cigarette smoking varied in different individuals. Treatment of pregnant rats with benzpyrene increased the activity of this hydroxylase in the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

1971
1971
1987
1987

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(59 citation statements)
references
References 8 publications
6
53
0
Order By: Relevance
“…1) (11). This finding is similar to the effects of smoking on human placental AHH activity (12)(13)(14). Since the AHH assay measures chiefly the formation ofbenzo[a]pyrene (BaP)-phenols, BaP metabolism in vitro was studied further by quantifying specific metabolites by high pressure liquid chromatography (HPLC) (11).…”
Section: Placental Metabolismsupporting
confidence: 88%
“…1) (11). This finding is similar to the effects of smoking on human placental AHH activity (12)(13)(14). Since the AHH assay measures chiefly the formation ofbenzo[a]pyrene (BaP)-phenols, BaP metabolism in vitro was studied further by quantifying specific metabolites by high pressure liquid chromatography (HPLC) (11).…”
Section: Placental Metabolismsupporting
confidence: 88%
“…may contribute to the development of certain birth defects (4,16,17). Although complex mixtures of chemicals contained in cigarette smoke have been described, little is known about the mechanisms by which these compounds may be embryopathic or about how the human conceptus can be protected from such chemical toxicity.In order to approach these problems, we have been studying the effects of maternal smoking on xenobiotic metabolism in human placenta, concentrating on AHH, a cytochrome P-450 monooxygenase system which increases its activity when mothers smoke (14,20,24,29,30). AHH catalyzes the first step in the metabolism of several of the toxins absorbed from cigarette smoke including PAHs.…”
mentioning
confidence: 99%
“…Since antipyrine is cleared almost entirely by hepatic biotransformation (Brodie and Axelrod, 1950), it seems likely that accelerated elimination of this drug is due to induction of the hepatic mixed function oxidases involved in drug metabolism. Previous studies in humans have shown that cigarette smoking is associated with increased activity of these enzymes in the placenta (Welch et al, 1968) and pulmonary alveolar macrophages (Cantrell et al, 1973).…”
Section: Introductionmentioning
confidence: 95%